Phenotypic and Functional Heterogeneity of Macrophages and Dendritic Cell Subsets in the Healthy and Atherosclerosis-Prone Aorta - Galkina, Elena V.; Butcher, Matthew J. (Frontiers in Physiology, 2012)
Atherosclerosis continues to be the leading cause of cardiovascular disease. Development of atherosclerosis depends on chronic inflammation in the aorta and multiple immune cells are involved in this process. Importantly, resident macrophages and dendritic cells are present within the healthy aorta, but the functions of these cells remain poorly characterized. Local inflammation within the aortic wall promotes the recruitment of monocytes and dendritic cell precursors to the aorta and micro-environmental factors direct the differentiation of these emigrated cells into multiple subsets of macrophages and dendritic cells. Recent data suggest that several populations of macrophages and dendritic cells can co-exist within the aorta. Although the functions of M1, M2, Mox and M4 macrophages are well characterized in vitro, there is a limited set of data on the role of these populations in atherogenesis in vivo. Recent studies on the origin and the potential role of aortic dendritic cells provide novel insights into the biology of aortic dendritic cell subsets and prospective mechanisms of the immune response in atherosclerosis. This review integrates the results of experiments analyzing heterogeneity of dendritic cells and macrophage subsets in healthy and diseased vessels and briefly discusses the known and potential functions of these cells in atherogenesis.